KEEFEKTIFAN MODEL NUMBERED HEADS TOGETHER (NHT) BERBANTUAN HANDOUT TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA PADA MATERI FUNGSI INVERS KELAS XI IPA MAN BATANG - M Saefularif (Universitas Pekalongan, 2016)
The result of the research showed that the experiment group has the average grade is 77,89, and the index can be gained z hitung = 2,836 > z tabel = 1,64 it means H 0 is dismissed (has reached the exchaustiveness). The result of the difference of two proportions test the thoroughness of the ability of solving problem, obtained z hitung = 2,31 > z tabel = 1,64, so H 0 is dismissed (the proportion of exchaustivenessthe ability of solving problem using NHT is more than conventional method). It can be concluded that the teachers must use the cooperatif method, especially with NHT model to improve the ability of solving problems for their students.